2015
DOI: 10.1002/jsfa.7181
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of biological activities of anthocyanin‐rich berry extracts on porcine intestinal epithelial cells

Abstract: We found that the chokeberry and elderberry extracts rich in cyanidin glycosides possess better antioxidant and anticytotoxic activities in comparison to blueberry or bilberry extracts with complex anthocyanin profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…In other studies it was shown that cyanidin O -sambubioside is the main compound in elderberry extract [ 13 , 14 , 15 ]. Kšonžekowá et al [ 16 ] determined the total anthocyanin content in extract of elderberry as equal to 483.7 mg/g of DM, while other literature data indicate a 8.33–101.40 mg/g of DW range [ 17 ], which are either much higher or lower than the value determined in the present work (136.96 mg/g of DW). To a large degree it depends on the method of extraction and type of reagents used.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…In other studies it was shown that cyanidin O -sambubioside is the main compound in elderberry extract [ 13 , 14 , 15 ]. Kšonžekowá et al [ 16 ] determined the total anthocyanin content in extract of elderberry as equal to 483.7 mg/g of DM, while other literature data indicate a 8.33–101.40 mg/g of DW range [ 17 ], which are either much higher or lower than the value determined in the present work (136.96 mg/g of DW). To a large degree it depends on the method of extraction and type of reagents used.…”
Section: Resultscontrasting
confidence: 77%
“…Antioxidant activity of elderberry extracts has been also confirmed in the current literature. The studies performed by Kšonžeková et al [ 16 ] confirmed the higher antioxidant status of elderberry extract, which is rich in cyanidin glycosides, compared to the activity of blueberry or bilberry extracts, and additionally indicated no cytotoxic effect on porcine intestinal epithelial cells. Studies by Bratu et al [ 37 ] inform, for example, that Sambucus nigra powder fruit extract in vitro has a very high antioxidant activity (quantified by a photoluminescence method), and no mutagenic effect at concentration below 0.1 g/dL, which makes it recommendable for application in food industry.…”
Section: Resultsmentioning
confidence: 94%
“…Elderberry displays a high concentration of compounds with antioxidative activity, especially anthocyanins, flavonoids and vitamins (Matejicek et al, 2015). Ksonzekova et al (2016) found that the chokeberry and elderberry extracts exhibit better antioxidant and anticytotoxic activ ities than blueberry or bilberry extracts with complex anthocyanin profile. Among the most common fruit and vegetables, elderberry is one of the richest in anthocyanins (Salamon et al, 2015) After preparation, the highest indicator of batter delamination was observed for the batter with no addition of fruit powders.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Vaccinium comprises a group of plants that includes up to 450 species; the fruits (berries) of many species are consumed by humans. The berries constitute a source of various bioactive phytonutrients, including phenolic compounds such as flavonoids, phenolic acids, lignans and polymeric tannins . Certain beneficial properties have been associated with the consumption of Vaccinium berries, such as antioxidant, antidiabetic, antihyperlipidemic, antiproliferative and neuroprotective activities …”
Section: Introductionmentioning
confidence: 99%